Environment Improvement Through Visual Street Art in Beting Village, Pontianak City: Perbaikan Lingkungan Kampung Kota Melalui Visual Street Art Di Kampung Beting Kota Pontianak - Wulandari*, Agustiah; Yuniarti, Erni; Pratiwi, Nana Novita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
BetingVillage is one of the urban sub-districts in Pontianak City, precisely in East Pontianak District. The local community views Kampung Beting with a negative image. This village looks busy and dirty because it was built on river water. Efforts that need to be made to improve the quality of the village environment are the PKM Activities for Improving the City Village Environment through Visual Street Art in Beting Village, Pontianak City. The aim of making visual street art is to beautify the village by painting the walls of residents' houses using bright colored paint.PKM is implemented using participatory and collaborative methods, starting from the preparation stage for determining the design, implementing wall drawings, and the final stage of socialization with the community. The image design concept chosen is Air Beting Village. The choice of street art design theme considered the characteristics of Kampung Beting as a sub-district where most of the residents' houses are above the water. This activity will add to the beauty of the environment and increase the attractiveness of Kampung Beting as a new tourist destination in Pontianak City